International variation in managing locally advanced or recurrent rectal cancer: prospective benchmark analysis. Issue 13 (12th August 2020) - Denost, Q.; Solomon, M.; Tuech, J.‐J.; Ghouti, L.; Cotte, E.; Panis, Y.; Lelong, B.; Rouanet, P.; Faucheron, J.‐L.; Jafari, M.; Lefevre, J. H.; Rullier, E.; et al.
Abstract : Background: Tumour extension beyond the mesorectal plane (ymrT4) occurs in 5–10 per cent of patients with rectal cancer and 10 per cent of patients develop locally recurrent rectal cancer (LRRC) after primary surgery. There is global variation in healthcare delivery for these conditions. Methods: An international benchmark trial of the management of ymrT4 tumours and LRRC was undertaken in France and Australia between 2015 and 2017. Heterogeneity in management and operative decision‐making were analysed by comparison of surgical resection rates, blinded intercountry reading of pelvic MRI, quality‐of‐life assessment and qualitative evaluations. Results: Among 154 patients (97 in France and 57 in Australia), 31·8 per cent had ymrT4 disease and 68·2 per cent LRRC. The surgical resection rates were 88 and 79 per cent in France and Australia respectively ( P  = 0·112). The concordance in operative planning was low (κ = 0·314); the rate of pelvic exenteration was lower in France than Australia both in clinical practice (36 of 78 versus 34 of 40; P  < 0·001) and in theoretical conditions (10 of 25 versus 50 of 57; P =  0·002). The R0 resection rate was lower in France than Australia for LRRC (25 of 49 versus 18 of 21; P =  0·007) but not for ymrT4 tumours (21 of 26 versus 15 of 15; P =  0·139). Morbidity rates were similar. Patients who underwent non‐exenterative procedures had higher scores on the mental functioning subscale at 12 months ( P  = 0·047), and a lower level of distress at 6 months ( P  = 0·049). Qualitative analysis highlighted five categories of psychosocial factors influencing treatment decisions: patient, strategy, specialist, organization and culture. Conclusion: This international benchmark trial has highlighted the differences in worldwide treatment of locally advanced and LRRC. Standardized care should improve outcomes for these patients. Abstract : An international benchmark trial of the management of ymrT4 and locally recurrent rectal cancer was undertaken in France and Australia between 2015 and 2017. This trial highlights the differences in worldwide treatment of locally advanced and locally recurrent rectal cancer. Standardized care should improve outcomes for these patients. Differences worldwide Abstract : Antecedentes: La extensión del tumor más allá del plano del meso‐rrecto (ymrT4) ocurre en el 5‐10% de los pacientes con cáncer de recto y el 10% de los pacientes desarrollan recidiva local del cáncer de recto ( locally recurrent rectal cáncer, LRRC) después de una cirugía primaria. Existe una variación global en la prestación de la asistencia sanitaria para esta pato‐logía. Métodos: Se realizó un ensayo de referencia internacional sobre el manejo de ymrT4 y LRRC en Francia y Australia entre 2015 y 2017. La heterogeneidad en el manejo y la toma de decisiones quirúrgicas se analizaron mediante la comparación de las tasas de resección quirúrgica, la lectura a ciegas de la resonancia magnética (RM) pélvica entre países, la evaluación de la calidad de vida y las evaluaciones cualitativas. Resultados: De 154 pacientes (97 en Francia versus 57 en Australia), el 32% tenía ymrT4 y el 68% tenía cáncer de recto con recidiva local. Las tasas de resección quirúrgica fueron del 87, 6% versus 77, 8% ( P = 0, 112). La tasa de concordancia en la decisión quirúrgica fue baja (coeficiente kappa = 0, 314) con una tasa más baja de exenteración pélvica en Francia, tanto en la práctica clínica (46% versus 85%; P < 0, 0001) como en condiciones teóricas (40% versus 88%; P = 0, 002). La tasa de resección R0 fue menor en Francia para la LRRC (51% versus 86%, P = 0, 007) pero no para el ymrT4 (81% versus 100%, P = 0, 139). Las tasas de morbilidad fueron similares. Los pacientes que se sometieron a procedimientos no exenterativos tuvieron una subescala de funcionamiento mental más alta a los 12 meses ( P = 0, 04) y un nivel de angustia más bajo a los 6 meses ( P = 0, 04). El análisis cualitativo destacó 5 categorías de factores psicosociales que afectaron a la decisión del tratamiento: paciente, estrategia, especialista, organización y cultura. Conclusión: Este ensayo de referencia internacional destaca las diferencias en el tratamiento mundial del cáncer de recto localmente avanzado y de la LRR. La aten‐ción estandarizada debería mejorar los resultados para estos pacientes.